Citizens, readers and local newspaper coverage of the 2005 UK general election - Cushion, Stephen (Javnost (Ljubljana), 2006)
In this article we examine how, in newspaper coverage of the 2005 general election, journalists set out not only to connect with the political lives of "ordinary" citizens but to find an active role for them to play in news space.In recent years, the sharp drop in electoral turnout has made many news organisations rethink the style and nature of political programming and publications, having come under considerable attack - from journalists, political elites and scholars - for not informing and engaging readers, listeners and viewers. Journalistic assessments of media coverage of the 2005 general election suggested that news organisations improved the way they engaged the needs of the "average citizen." Even to the extent where, according to one senior journalist, "getting closer to the real people got outof hand." We enter this debate by looking systematically at the role citizens played in the 2005 general election in regional and local newspapers'coverage. We examined every kind of source in election coverage - from police, politicians and pressure groups to citizens, business leaders andacademics. Overall, we question the success of the regional and local pressin achieving the type and level of engagement implied by many of the UK'smost distinguished journalists in post-election analysis. We conclude thatfinding ways to "get closer to the real people" remains a goal yet to be achieved despite journalistic protestations.
Keywords: Velika Britanija; volitve; election; 2005; mass media; množični mediji; časniki; obveščanje; informiranje; vpliv